2021
DOI: 10.1002/eng2.12410
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating higher photovoltaic penetration in residential distribution networks using demand side management and active voltage control

Abstract: Future power networks are certain to have high penetrations of renewable distributed generation such as photovoltaics (PV). At times of high PV generation and low customer demand (e.g., summer), network voltage is likely to rise beyond limits mandated by grid codes resulting in a curtailment of PV generation, unless appropriate control means are used. This leads to a reduction in energy yield and consequently reduces the economic viability of PV systems. This work focuses on scenario-based impact assessments u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 50 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…Electricity utilities adopt DSM as a technique to regulate demand by motivating consumers to adjust their electricity consumption level and pattern. Gobind Pillai et al [12] showed that even though DSM could be a preferred method due to its potential for deployment through comprehensive demand response initiatives in countries, technically it is not effective in avoiding PV energy curtailment because of a weaker low-voltage network with higher solar resources. Distribution system operation (DSO) ensures the stability of the grid and power quality at a low voltage level.…”
Section: Introductionmentioning
confidence: 99%
“…Electricity utilities adopt DSM as a technique to regulate demand by motivating consumers to adjust their electricity consumption level and pattern. Gobind Pillai et al [12] showed that even though DSM could be a preferred method due to its potential for deployment through comprehensive demand response initiatives in countries, technically it is not effective in avoiding PV energy curtailment because of a weaker low-voltage network with higher solar resources. Distribution system operation (DSO) ensures the stability of the grid and power quality at a low voltage level.…”
Section: Introductionmentioning
confidence: 99%
“…Again, that is analysed from the perspective of the globe or of a region [Tol 2000;Baker 2021;Knuth 2021], separate states [Tanaka et al 2017;Williams et al 2021] as well as locally [Kennedy, Stock 2021]. Another important area of analysis for my deliberations here is the network cost of RES, which is represented in a large number of publications [Mai et al 2012;Mai et al 2013;D'haeseleer 2013;Fraunhofer 2015;ARE 2016;Al Matin et al 2019;Burger et al 2019b;Karkour et al 2020;Pillai et al 2021;Falvo et al 2021;Veronese et al 2021;Yang et al 2022]. This literature review will be continued in the series of next articles that I plan, first by adding country-specific debates in articles covering transformation experiences of selected developed countries and by the Polish literature on the various possible scenarios for the future of the Polish energy mix, that I plan in the last article of the series.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%